Customer Satisfaction Through Brand Trust in Mixue: Hedonic and Product Innovation - Cynthia, Rosabella; Tuti, Meylani (Asian Journal of Management Analytics, 2023)
The goal of this study is to determine how hedonic and creative product effects affect consumer happiness and brand trust. A survey that was delivered to Mixue customers using a purposive sample strategy was the research method employed. 222 people were sampled. The Structural Equation Model is used in the data analysis technique with the use of smart pls 3 software. The findings demonstrate that hedonistic and innovative goods have a large direct and indirect impact on brand trust and consumer happiness. To draw deeper inferences about brand trust and consumer pleasure, many more factors than product innovation and hedonic analysis might be included in the future study.